PROPOSED BUSINESS STARTEGY TO INCREASE STUDENT ENROLMENT OF MASTER OF INDUSTRIAL PHARMACHY OF XYZ UNIVERSITY - Rusbagja, Muhammad Zidane; Wandebori, Harimukti (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The declining enrollment in the Master of Industrial Pharmacy (MFI) program at XYZ UNIVERSITY has become a critical issue, it needed a strategic way to ensure sustainability in a competitive academic landscape. This research seeks to explore and address the declining enrolment by analyzing both internal and external factors affecting the program. Leveraging frameworks such as value chain analysis, resource evaluation, Five Industry Forces, and general environment analysis, this study aims to identify strengths, weaknesses, opportunities, and threats to develop actionable strategies. The research use qualitative methods, including interviews and document reviews, to collect data on institutional capabilities, external market forces, and student expectations. Through TOWS analysis and strategic planning, the study proposes solutions to enhance the program’s visibility, align curriculum offerings with industry demands, and improve overall competitiveness. The outcomes are expected to contribute to the academic literature on strategic management in higher education and offer practical insights for addressing enrolment challenges in specialized programs.